2015
DOI: 10.1155/2015/196589
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Proteomics Reveals Involvement of Phosphorylated HSP27 in the Pathogenesis of Osteoporosis

Abstract: Peripheral monocytes, precursors of osteoclasts, have emerged as important candidates for identifying proteins relevant to osteoporosis, a condition characterized by low Bone Mineral Density (BMD) and increased susceptibility for fractures. We employed 4-plex iTRAQ (isobaric tags for relative and absolute quantification) coupled with LC-MS/MS (liquid chromatography coupled with tandem mass spectrometry) to identify differentially expressed monocyte proteins from premenopausal and postmenopausal women with low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
(31 reference statements)
0
18
0
Order By: Relevance
“…There has been some genome-wide transcriptomics analysis [ 6 , 13 , 14 ] of individual monocyte subsets, but less information at the protein level is available. Most proteomic analyses performed on monocytes have used monocyte derived cell lines or with the whole monocyte population [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Wong’s group have carried out proteomic analysis on purified monocyte populations [ 43 , 44 ], where they used iTRAQ to determine differences between cell populations.…”
Section: Resultsmentioning
confidence: 99%
“…There has been some genome-wide transcriptomics analysis [ 6 , 13 , 14 ] of individual monocyte subsets, but less information at the protein level is available. Most proteomic analyses performed on monocytes have used monocyte derived cell lines or with the whole monocyte population [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Wong’s group have carried out proteomic analysis on purified monocyte populations [ 43 , 44 ], where they used iTRAQ to determine differences between cell populations.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen-containing bisphosphonate can potently inhibit the prenylation and function of GTP-binding proteins required for osteoclast formation and now is firmly established as first-line therapy for osteoporosis (Grey and Reid, 2006). TUBB6 plays a key role in GTP binding and has been associated with BMD variation (Daswani et al, 2015 NSUN4, C11orf83, PDSS2, PACS2, NDUFV3, and ALDH3B1), 6 DMC-annotated genes (PPARGC1A, ILKAP-PER2, SIRT6, RTEL-TNFRSF6B, VARS2-GTF2H4, and MFN2-TNFRSF8-TNFRSF1B), and 3 metabolites biomarkers ({4-((E)-2-(2,3,5-trihydroxyphenyl)ethenyl)phenyl}oxidanesulfonic acid, Acetyl-T2 toxin, and LysoPC (16:0)) associated with telomere/mitochondrial activity. TERF1 encodes a component of the telomere nucleoprotein complex, which can regulate telomere elongation and plays a key role in aging-related disease (Blasco, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we used iTRAQ based quantitative proteomics approach to study monocytes from premenopausal and postmenopausal Indian women with low versus high BMD, all in a single experimental platform using 4-plex iTRAQ coupled to nano-LC-MS/MS [ 42 ]. We found that heat shock protein 27, also known as heat shock protein beta-1 (HSPB1), was distinctly upregulated in low BMD condition in both premenopausal and postmenopausal categories [ 42 ]. Validation revealed that total HSP27 (tHSP27) and phosphorylated HSP27 (pHSP27) were elevated in low BMD condition in both categories not only in monocytes but also in sera [ 42 , 43 ].…”
Section: Monocyte Protein Profiling In Low Versus High Bmd Conditimentioning
confidence: 99%